2020
DOI: 10.1021/acsanm.0c01088
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dot–MnO2 Nanosphere Composite Sensors for Selective Detection of Glutathione

Abstract: Herein, a fluorescent nanosensor based on carbon dots (Cdots) and different-size MnO2 nanospheres has been synthesized for rapid detection of glutathione (GSH). Water-soluble and highly fluorescent Cdots were prepared by the microwave method using ascorbic acid as the precursor. MnO2 nanospheres of different sizes (large, medium, and small) were prepared by varying the concentration ratio of methionine and KMnO4 at room temperature, which was confirmed by HRTEM analysis. The different sizes of MnO2 nanospheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…The experimental results indicated that the emission wavelength lies in the range from 425 to 450 nm, whereas in several reports oxygen-rich CDs have emission at 420 nm. 42 The results indicated that nitrogen passivation leads to a bathochromic shi in the emission spectra of NCDs. The descending order of the bathochromic shi for NCDs is as follows: U-NCDs > C-NCDs > G-NCDs > T-NCDs (Fig.…”
Section: Optical Properties Of Different Ncdsmentioning
confidence: 95%
“…The experimental results indicated that the emission wavelength lies in the range from 425 to 450 nm, whereas in several reports oxygen-rich CDs have emission at 420 nm. 42 The results indicated that nitrogen passivation leads to a bathochromic shi in the emission spectra of NCDs. The descending order of the bathochromic shi for NCDs is as follows: U-NCDs > C-NCDs > G-NCDs > T-NCDs (Fig.…”
Section: Optical Properties Of Different Ncdsmentioning
confidence: 95%
“…110 Besides these metal ions, small organic molecules, proteins, and macromolecules also play very important roles in the biological, medical, and environmental systems. [111][112][113] There are various insecticides or pesticides etc. which affect the environment and their detection is needed.…”
Section: Sensing Applicationmentioning
confidence: 99%
“…Recently, we have developed a fluorescent nanoprobe that consists of Cdots and different-size MnO 2 NSPs for ultrasensitive detection of GSH. 29 We studied the different photophysical parameters such as quantum yield, average lifetime values, radiative rate constant, nonradiative rate constant, rate of electron transfer, the efficiency of electron transfer, FRET efficiency, and Forster distance. We also determined the photoluminescence (PL) properties of Cdots and found that the variation in size affects the performance of MnO 2 in the sensing ability of GSH.…”
Section: ■ Introductionmentioning
confidence: 99%